PENGARUH SPESIALISASI AUDITOR DAN REPUTASI KAP TERHADAP AUDIT REPORT LAG (Studi pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Tahun 2015-2017) - Irin Sukma Hati; Herry Laksito (Diponegoro Journal of Accounting, 2019)
The purpose of this research is to examines the relation between auditor specialization and the public accountant firm reputation to audit report lag to the manufacturing companies listed on the Indonesia Stock Exchange year 2015-2017. The dependant variable in this research is audit report lag. The independent variables in this research are auditor specialization and public accountant firm reputation. The control variables in this research are companies size, leverage ratio, subsidiary, loss, and industry.The sample consists of 298 financial reports from the manufacturing companies listed on the Indonesia Stock Exchange year 2015-2017. Secondary data used in this research and selected by using purposive sampling method. The analysis method that was used in this research was multiple linear regression. Classical assumption tests was done before conducted the regression test.The results of this research is both of the independent variables, auditor specialization and public accountant firm reputation, have negative and significant influence to audit report lag.